Robots, Industry 4.0 and Humans, or Why Assembly Work Is More than Routine Work - Sabine Pfeiffer (Societies, 2016)
This article condenses the key findings of qualitative studies on assembly work. Grounded conceptually in considerations of the role of experiential knowledge and living labor capacity with regard to informal expertise and tacit knowledge, the empirical results challenge the dominant view of assembly work as routine tasks that could easily be replaced by robotics. The empirical basis comprised of 62 qualitative interviews in five assembly plants provides answers to two questions: Are there non-routine aspects to be found in assembly work today? What exactly is the nature of experience in assembly work? The detailed research results are presented in three steps: the first focuses on the role of the non-routine in core assembly tasks; the second discusses the important and increasing role played by interactive capabilities in assembly work to ensure high performance, quality, and a smooth material flow; and the third highlights the usually neglected role of assembly workers in processes of innovation and organizational learning. The concluding chapter discusses the findings from the perspective of new technological options in robotics, possible worker resistance and effects on employment.